Effects of indirubin and isatin on cell viability, mutagenicity, genotoxicity and BAX/ERCC1 gene expression - Fogaca, Manoela Viar; Candido-Bacani, Priscila de Matos; Benicio, Lucas Milanez; Zapata, Lara Martinelli; Cardoso, Priscilla de Freitas; Oliveira, Marcelo Tempesta de; Calvo, Tamara Regina [UNESP]; Varanda, Eliana Aparecida [UNESP]; Vilegas, Wagner [UNESP]; Syllos Colus, Ilce Mara de (Taylor & Francis Ltd, 2017)
Context: Indigofera suffruticosa Miller (Fabaceae) and I. truxillensis Kunth produce compounds, such as isatin (ISA) and indirubin (IRN), which possess antitumour properties. Their effects in mammalian cells are still not very well understood. Objective: We evaluated the activities of ISA and/or IRN on cell viability and apoptosis in vitro, their genotoxic potentials in vitro and in vivo, and the IRN-and ISA-induced expression of ERCC1 or BAX genes. Materials and methods: HeLa and/or CHO-K1 cell lines were tested (3 or 24 h) in the MTT, Trypan blue exclusion, acridine orange/ethidium bromide, cytokinesis-blocked micronucleus (CBMN) and comet (36, 24 and 72 h) tests after treatment with IRN (0.1 to 200 mu M) or ISA (0.5 to 50 mu M). Gene expression was measured by RT-qPCR in HeLa cells. Swiss albino mice received IRN (3, 4 or 24 h) by gavage (50, 100 and 150 mg/kg determined from the LD50 - 1 g/kg b.w.) and submitted to comet assay in vivo. Results: IRN reduced the viability of CHO-K1 (24 h; 5 to 200 mu M) and HeLa cells (10 to 200 mu M), and was antiproliferative in the CBMN test (CHO-K1: 0.5 to 10 mu M; HeLa: 5 and 10 mu M). The drug did not induce apoptosis, micronucleus neither altered gene expression. IRN and ISA were genotoxic for HeLa cells (3 and 24 h) at all doses tested. IRN (100 and 150 mg/kg) also induced genotoxicity in vivo (4 h). Conclusion: IRN and ISA have properties that make them candidates as chemotherapeutics for further pharmacological investigations.
Keywords: Indigofera suffruticosa; Indigofera truxillensis; HeLa cells; CHO-K1 cells; cytokinesis-blocked micronucleus assay; comet assay; apoptosis